DMRT1 regulates human germline commitment - Irie, N; Lee, S-M; Lorenzi, V; Xu, H; Chen, J; Inoue, M; Kobayashi, T; Sancho-Serra, C; Drousioti, E; Dietmann, S; Vento-Tormo, R; Song, C-X; et al. (Springer Nature, 2023)
Germline commitment following primordial germ cell (PGC) specification during early human development establishes an epigenetic programme and competence for gametogenesis. Here we follow the progression of nascent PGC-like cells derived from human embryonic stem cells in vitro. We show that switching from BMP signalling for PGC specification to Activin A and retinoic acid resulted in DMRT1 and CDH5 expression, the indicators of migratory PGCs in vivo. Moreover, the induction of DMRT1 and SOX17 in PGC-like cells promoted epigenetic resetting with striking global enrichment of 5-hydroxymethylcytosine and locus-specific loss of 5-methylcytosine at DMRT1 binding sites and the expression of DAZL representing DNA methylation-sensitive genes, a hallmark of the germline commitment programme. We provide insight into the unique role of DMRT1 in germline development for advances in human germ cell biology and in vitro gametogenesis.